New charge-transfer complexes of 1, 2, 5-chalcogenadiazoles with tetrathiafulvalenes. Issue 3 (9th December 2022) - Chulanova, Elena A.; Radiush, Ekaterina A.; Balmohammadi, Yaser; Beckmann, Jens; Grabowsky, Simon; Zibarev, Andrey V.
Abstract : Despite noteworthy charge transfer and numerous intermolecular interactions, the title complexes (chalcogen = S, Se and Te) are weakly bonded; the most important contributions to the interaction energy are of dispersion and electrostatic nature. Abstract : Five new charge-transfer (CT) complexes of structurally varied 1, 2, 5-chalcogenadiazoles (monocyclic, 6-5 bicyclic and 6-6-5 tricyclic; chalcogen = S, Se and Te) with tetrathiafulvalenes (TTF and its bis(ethylenedithio) derivative BEDT-TTF) were obtained by co-crystallization of donor and acceptor components and characterized by X-ray diffraction and UV-vis spectroscopy in combination with density functional theory calculations. Bonding analyses were carried out with the quantum theory of atoms in molecules and Hirshfeld surface and non-covalent interaction analyses, accompanied by calculations of model energies of molecular pairs. According to these calculations, the complexes are rather weakly bonded by predominantly electrostatic interactions with significant contributions from dispersion interactions. The main structural motifs are assigned to π-stacking interactions and σ-hole driven hydrogen and chalcogen bonding. CT magnitudes vary between 0.09 and 0.37 e, and the CT bands in the UV-vis spectra of the complexes lie in the range of 550–750 nm.